Curves and lattices of points in the minkowski plane (1991)
The main goal of this work is to derive an integral formula refering to bounded convex sets (section 3), in order to obtain some results involving lattices of points in the Minkowski plane (seccion 4). To prove such a formula it is necessary to develop some tools of differential geometry in the large. This is done in section 2, where the turning tangents theorem for Euclidean curves is carried over to Minkowski plane.